Enhanced dipicolinic acid production during the stationary phase in Bacillus subtilis by blocking acetoin synthesis. Issue 12 (2nd December 2015) - Toya, Yoshihiro; Hirasawa, Takashi; Ishikawa, Shu; Chumsakul, Onuma; Morimoto, Takuya; Liu, Shenghao; Masuda, Kenta; Kageyama, Yasushi; Ozaki, Katsuya; Ogasawara, Naotake; Shimizu, Hiroshi
Abstract: Bacterial bio-production during the stationary phase is expected to lead to a high target yield because the cells do not consume the substrate for growth. Bacillus subtilis is widely used for bio-production, but little is known about the metabolism during the stationary phase. In this study, we focused on the dipicolinic acid (DPA) production by B. subtilis and investigated the metabolism. We found that DPA production competes with acetoin synthesis and that acetoin synthesis genes ( alsSD ) deletion increases DPA productivity by 1.4-fold. The mutant showed interesting features where the glucose uptake was inhibited, whereas the cell density increased by approximately 50%, resulting in similar volumetric glucose consumption to that of the parental strain. The metabolic profiles revealed accumulation of pyruvate, acetyl-CoA, and the TCA cycle intermediates in the alsSD mutant. Our results indicate that alsSD -deleted B. subtilis has potential as an effective host for stationary-phase production of compounds synthesized from these intermediates. Graphical abstract: : Dipicolinic acid production in B. subtilis during the stationary phase. The deletion of alsSD enhanced the dipicolinic acid productivity by 1.4-fold.